Pengaruh Pupuk Vermikompos Pada Tanah Inceptisol Terhadap Pertumbuhan dan Hasil Sawi Hijau (Brassica juncea L) - Herry Dhani; Wardati '; Rosmimi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Mustard is one of broadleaf vegetables are very potential to be cultivated because of the high demand of vegetables. production is likely to increase over the use of inorganic fertilizers and pesticides excessive. At the now widely circulated one is organic fertilizer vermicompost. Provision of vermicompost on soil can improve soil chemical properties, soil physical properties and biological properties of soil. This research was conducted in the Faculty of Agriculture experimental station, Riau University, campus Bina Widya km 12, 5, Tampan, Pekanbaru, with soil type Inceptisol, from March until May 2013. This study uses a completely randomized design (RAL) with 5 treatments and 5 replicates in order to obtain 25 units of the experiment, namely T0: without giving vermicompost, T1:2ton/ha vermicompost, T2: 4 tons / ha vermicompost, T3: 6ton/ha vermicompost, T4 : 8ton/ha vermicompost. Parameters observed in this study were plant height, number of leaves, leaf area, root volume, and fresh weight of consumption. vermicompost fertilizer on soil of Inceptisol significant effect on the growth parameters of plant height, leaf number, leaf area, and heavy consumption of fresh mustard plant and not a real effect on the root volume. Keyword: Mustard greens, Vermicompost fertilizer, Soil inceptisol.